2008
DOI: 10.1086/592228
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Galaxy Formation with Stellar Halos. II. Relating Substructure in Phase and Abundance Space to Accretion Histories

Abstract: This paper explores the mapping between the observable properties of a stellar halo in phase and abundance space and the parent galaxy's accretion history in terms of the characteristic epoch of accretion and mass and orbits of progenitor objects. The study utilizes a suite of 11 stellar halo models constructed within the context of a standard ÃCDM cosmology. The results demonstrate that coordinate-space studies are sensitive to the recent (0Y8 Gyr ago) merger histories of galaxies (this timescale corresponds … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
500
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(549 citation statements)
references
References 68 publications
38
500
1
Order By: Relevance
“…In the solar neighbourhood the change of the [O/Fe] The [α/Fe] distribution function of surviving satellites versus that of the inner halo was already modelled in detail by Font et al (2006a), who also concluded that the bulk of the halo formed from massive satellites accreted early on. As noted by Font et al (2006b) and Johnston et al (2008) we see that in our models the net efficiency of star formation -and in particular the difference therein between the building blocks and satellites -shows some variations between the modelled Milky Way-like systems. This means that, largely independent of the assumptions made for the exact delay time distributions and/or Fe-enrichment mechanisms, we might expect to see different [α/Fe] distributions in various Milky Way-mass systems depending on their detailed formation histories.…”
Section: Relation Between Iron Abundance and Supernovae Type Ia Delaysupporting
confidence: 71%
“…In the solar neighbourhood the change of the [O/Fe] The [α/Fe] distribution function of surviving satellites versus that of the inner halo was already modelled in detail by Font et al (2006a), who also concluded that the bulk of the halo formed from massive satellites accreted early on. As noted by Font et al (2006b) and Johnston et al (2008) we see that in our models the net efficiency of star formation -and in particular the difference therein between the building blocks and satellites -shows some variations between the modelled Milky Way-like systems. This means that, largely independent of the assumptions made for the exact delay time distributions and/or Fe-enrichment mechanisms, we might expect to see different [α/Fe] distributions in various Milky Way-mass systems depending on their detailed formation histories.…”
Section: Relation Between Iron Abundance and Supernovae Type Ia Delaysupporting
confidence: 71%
“…Iron abundances of accreted populations are related to the masses of the dwarf progenitors (e.g., see Johnston et al 2008;Kirby et al 2013). If our 13 stars are accreted halo stars, measuring iron abundances may help to determine whether a single accretion event or several are responsible for the shell-type structure we observe, and we can use the abundances to estimate the mass(es) of the progenitor(s).…”
Section: Chemistrymentioning
confidence: 99%
“…Numerical simulations have been performed to examine observable consequences of this process, implementing prescriptions of both the assembly of dark matter halos and star formation within these halos Robertson et al 2005;Font et al 2006aFont et al , 2006cDe Lucia & Helmi 2008;Cooper et al 2010). These studies generally suggest that the accreted galaxies imprint distinct substructures in both phase-space and chemical abundance space for many gigayears (Font et al 2006b;Johnston et al 2008), demonstrating that the kinematics and chemical abundances are an important tracer of the merging history of the Galaxy.…”
Section: Introductionmentioning
confidence: 99%